Application of the wheel reflective cracking test for assessing geosynthetics in anti-reflection pavement cracking systems. Issue 5 (October 2007) - Prieto, J. N.; Gallego, J.; Pérez, I.
Abstract : The reflective cracking phenomenon occurs when joints and cracks in a pavement that is generally made of concrete or cement-treated layers propagate up through the asphalt overlay and appear on the pavement surface. These cracks allow water to enter and cause the pavement deterioration process to accelerate, thereby increasing maintenance costs. The wheel reflective cracking (WRC) test permits the crack reflection strength of asphalt overlays and anti-reflection systems incorporating an asphalt-impregnated geotextile to be assessed. The test apparatus simultaneously applies the tensile, flexural and shear stresses in the vicinity of the pavement crack. This article describes the WRC test, and reports on a statistical study of the results obtained using different asphalt overlays and anti-reflection crack systems with and without reinforcing geosynthetic products. Each anticrack solution is analysed according to two criteria: (1) time to failure; and (2) the configuration of the cracked area after specimen failure. This second criterion is of practical concern, because it is related to the expected rate of deterioration of the cracked area in a field pavement and the level of difficulty in remediating the cracking as part of road maintenance.